MENINJAU ULANG SISTEM PEMBINAAN NARAPIDANA KORUPSI DI INDONESIA - Nimerodi Gulo (Universitas Muhammadiyah Kotabumi, 2019)
Indonesia continues to improve its efforts to eradicate corruption which is in fact an extraordinary crime. Corruption requires extra treatment not only in the process of law enforcement but also the process of fostering corruption inmates. So far, the existing laws and regulations have not clearly regulated the concept of good coaching, especially for corruption convicts as a result of corruption inmates are still free to use resources and influence to be able to obtain various facilities that actually conflict with existing regulations. The problems that will be raised in this article are: First, how is the system of guiding corruption inmates in several countries? Second, how is the concept of fostering corruption prisoners better for Indonesia. This article uses a normative approach through the study of literature or literature. This article concludes the model of fostering prisoners in particular corruption prisoners in Penitentiary has not run as expected. Departing from the comparison of prisoner development models in various countries, we need a different approach to fostering models both for public inmates and corruption accordingly. It is necessary to improve and synchronize efforts to foster corruption inmates, both institutional structures, the substance of RI Law No.12 of 1995 and the culture of stakeholders to be able to provide adequate solutions for fostering corruption inmates.